In vitro removal of anti-infective agents by a novel cytokine adsorbent system. Issue 2 (February 2019) - König, Christina; Röhr, Anka C; Frey, Otto R; Brinkmann, Alexander; Roberts, Jason A; Wichmann, Dominic; Braune, Stephan; Kluge, Stefan; Nierhaus, Axel
Objectives: The aim of this study is to describe the in vitro adsorption of anti-infective drugs onto an extracorporeal cytokine adsorber. Methods: Various anti-infective drugs (β-lactams, quinolones, aminoglycosides, glycopeptides, azole antimycotics) were prepared in normal saline 0.9% and human albumin 5%, and pumped through a cytokine cartridge (CytoSorb ® ; CytoSorbents Corporation, Monmouth Junction, NJ, USA) at a flow rate of 1.2 L/h for 1.5 h. In addition, meropenem and ciprofloxacin were dissolved in reconstituted blood and run through a CytoSorb cartridge, which was integrated into a continuous renal replacement therapy circuit with a flow rate of 2 L/h for 18 h. Samples from the solution, pre- and post-filter, were quantified by high-performance liquid chromatography with ultraviolet detection and fluorescence polarisation immunoassay. Results: Observed mean clearance of the drugs in normal saline was 1.22 ± 0.07 L/h. In human albumin, clearance was 1.29 ± 0.08 L/h. In reconstituted blood, clearance of meropenem decreased from 5.4 to 1.4 L/h and for ciprofloxacin from 6.3 to 4.3 L/h within the first 1.5 h because of early drug adsorption. Continuous renal replacement therapy clearance measured without CytoSorb was stable at 2 and 1.7 L/h, respectively. Approximately 400 mg of meropenem and 300 mg of ciprofloxacin had been adsorbed by CytoSorb, suggesting that these amounts are the maximum adsorptive capacity for these drugs. Conclusion: In these settings, all tested drugs were adsorbed by the cartridge in relevant amounts. The identified maximum adsorptive capacity and the rapid decline in concentration during the first 1.5 h of CytoSorb use suggest that the administration of an additional dose within the first hours of CytoSorb treatment may be reasonable. In addition, early therapeutic drug monitoring should be considered.